Changes in immunity characteristics in patients with small (T1) choroidal melanoma after a course of 810-nm diode laser TTT delivered using the developed methodology - I.V. Tsukanova; S.I. Poliakova; L.N. Velichko; A.V. Bogdanova (Ukrainian Society of Ophthalmologists, 2019)
Background: Immune response is an important factor for efficacy of choroidal melanoma (CM) treatment. Adequate uveal melanoma (UM) organ-saving treatment and treatment efficacy monitoring requires determining the interaction pattern between immune and tumor cells. Purpose: To investigate changes in immune characteristics in patients with small T1 CM (measuring ? 3 mm in thickness and ? 12 mm in basal dimension) after a course of 810-nm diode laser transpupillary thermotherapy (TTT) delivered using the developed methodology. Materials and Methods: We determined immune system characteristics in 35 patients (9 men (25.7%) and 26 women (24.3%); mean age, 53.9 (12.1) years) with small (T1) CM before and after a course of 810-nm diode laser TTT delivered using the developed methodology. Results: Some characteristics (absolute white blood cell count, absolute and relative CD8+ T cell counts, absolute and relative phagocytic neutrophil activity, absolute and relative CD19+ B cell counts, IgA, IgM, and IgG) decreased, whereas others (relative white blood cell count, absolute and relative CD3+ T cell counts, absolute and relative CD4+ T helper counts, CD4+/CD8+ T-cell ratio, and absolute and relative CD16+ NK cell counts) increased after treatment. However, these changes were not statistically significant, excepting that relating to CD4+/CD8+ T-cell ratio (F=7.9; p = 0.05). Conclusion: 810-nm diode laser transpupillary thermotherapy (TTT) delivered using the developed methodology results in a shift in specific antitumor immune response patterns with a suppression of cytolytic CD8+ T cell response, which requires administering immunocorrective therapy as early as the initial stage of the disease.